Kadar Glukosa Darah, Diet dan Terapi Antihiperglikemia Pada Pasien Diabetes Melitus dengan Ulkus Diabetikum yang di Rawat Rumah Sakit: Blood Glucose Level, Diet and Antihyperglycemic Therapy in Patient with Diabetes and Diabetic Ulcers in Hospital - Novia Putri, Rima; Deliana, Muthia; Pusparianda, Dewi (Poltekes Kemenkes Tanjungpinang, 2024)
Type 2 diabetes mellitus (T2DM) is a chronic disease often accompanied by serious complications, such as diabetic ulcers. Poorly controlled blood glucose levels can worsen patient outcomes. This study aims to describe blood glucose levels, diet, and antihyperglycemic therapy in T2DM patients with diabetic ulcers in Tanjungpinang City. This descriptive observational study was conducted on 56 diabetic ulcer patients hospitalized in two hospitals in Tanjungpinang City. Data were collected from medical records and HbA1c laboratory tests. Variables analyzed included blood glucose levels, diet, and antihyperglycemic therapy. Univariate analysis was performed using percentages. The majority of patients (94.6%) had uncontrolled blood glucose levels (HbA1c >7%), with 60.7% having HbA1c ≥10%. Most patients (83.9%) were on a diabetic diet, although a few patients were not on a diabetic diet. Insulin was the most common antihyperglycemic therapy (58.9%). Patient characteristics showed a predominance of females (69.6%), normal nutritional status (62.5%), and diabetic ulcer severity at grade 4 (55.4%). Most diabetic ulcer patients in Tanjungpinang City have poorly controlled blood glucose levels despite receiving insulin therapy and a diabetic diet. This highlights the need for a more comprehensive approach to blood glucose management. Comprehensive interventions are required to improve blood glucose control, expedite diabetic ulcer healing, and enhance patient quality of life.